The Stone Age News - Macdonald, Fiona (Milwaukee, Wisconsin Gareth Stevens Publishing, 2001)
Uses a newspaper format to present the inventions, lifestyles, climate changes, and progress in hunting and farming of the Stone Age.
Includes Index
Keywords: Stone Age -- Juvenile literature; Prehistoric peoples -- Juvenile literature; Prehistoric peoples